Education for Breastfeeding Mothers with Hypoglycemia - Yuliana; Idawati; Meliani Sukmadewi Harahap (Universitas STRADA Indonesia, 2025)
Hypoglycemia is a pathological condition with blood glucose levels showing a value of < 70 mg/dl or < 3.9 mmol/L accompanied by clinical symptoms in the patient. Hypoglycemia in breastfeeding mothers can cause several impacts, including disruption of breast milk production, fatigue, stress and nutritional balance disorders. The 2023 Indonesian Health Survey found that hypoglycemia is more commonly found, both in the productive age group (18-59 years) and the elderly (60 years and above). The percentage of hypoglycemia was found in 52.1% of the productive age group, and in 48.9% of the elderly age group. The purpose of this community service is to provide health education to breastfeeding mothers with hypoglycemia. The method that will be used in this community service activity is education for breastfeeding mothers. The results of the analysis showed that the mother had hypoglycemia since adolescence, irregular sleep patterns and the mother often consumed caffeine, irregular diet, due to the irregular lifestyle so that an examination was carried out and the results of the mother's glucose reached 56 mg/dl, the results showed that the mother's glucose was low, education was carried out on the mother, the results of the mother's knowledge increased and had begun to implement a healthy lifestyle, The mother did not consume caffeine and a glucose test was carried out at 105 mg/dl.